The Widow's Might - Breyer, Chloe (Journal of religion and health, 2004)
Jesus' teaching about the value of the poor widow's offering to the Temple both praises her generosity and laments the unjust religious and social system of which she is a part. The author finds this double-edged truth relevant in the way the United States relates to poor countries like Afghanistan.